Analisis Dampak Kenaikan Suku Bunga Bank Indonesia terhadap Kinerja Keuangan Perusahaan Sektor Perbankan di Indonesia - Nur Hesthria (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2025)
Bank Indonesia’s interest rate policy is a key instrument in maintaining monetary stability and has direct implications for the performance of the banking sector. An increase in the policy interest rate may affect banks’ intermediation function, profitability, liquidity, and overall risk exposure. This study aims to analyze the impact of Bank Indonesia’s interest rate increases on the financial performance of banking sector companies in Indonesia. The research employs a quantitative approach using secondary data obtained from the financial statements of banks listed on the Indonesia Stock Exchange during the study period. Financial performance is examined through key indicators, including profitability, liquidity, and credit risk. The results indicate that increases in Bank Indonesia’s interest rate have a significant effect on the financial performance of banks. On the one hand, higher interest rates tend to enhance interest income and improve bank profitability; on the other hand, they may suppress credit growth and increase the risk of non-performing loans. These findings suggest that the impact of interest rate policy on banking financial performance is multidimensional and requires effective risk management. This study is expected to contribute to the development of financial literature and provide insights for banking practitioners and policymakers in responding to changes in monetary policy in Indonesia.